Traction prediction equations for riceland type tyre - Khidir, Elwaleed Awad; Yahya, Azmi (Universiti Putra Malaysia, 1999)
A study was conducted to determine the accuracy of Wismer-Luth’s and Brixius’ equations in predicting motion resistance ratio, net traction ratio and tractive efficiency of a riceland type tyre. The tyre was tested on a sandy clay loam soil in an indoor UPM tyre traction testing facility. The experiment was conducted by running the tyre in two operation modes; towing mode for formulation of tyre motion resistance ratio equation and driving mode for the formulation of the tyre net traction ratio and tractive efficiency equations. A total of ninety test runs were involved in the tyre motion resistance ratio determinations at three selected inflation pressures (i.e 221, 193 and 166 kPa) and selected wheel numerics ranging between 0 to 70. For the tyre net traction and tractive efficiency determinations, 126 test runs were conducted in a combination consisting of three selected inflation pressures namely (i.e 221, 193 and 166 kPa) and two wheel numerics (i.e 19 and 29) representing two extreme types of soil strength under different levels of travel reduction ranging between 0 to 40%. New equations were formulated using regression analysis to describe the tyre motion resistance ratio, torque ratio and net traction ratio. Analysis of covariance (ANCOVA) showed that the effect of tyre inflation pressure was highly significant at 0.01 probability level for both the tyre motion resistance ratio and tyre net traction ratio. The advantage of lower tyre inflation pressure was pronounced when decreasing the tyre nominal inflation pressure (i.e 221 kPa) to 193 kPa. However, the traction performance of the tyre was worst at inflation pressure of 166 kPa.